Mitigasi Bencana dengan Monitoring Air di Daerah Aliran Sungai Kampwolker - Deliana Mangisu; Aris Sampe (Universitas Islam Raden Rahmat, Malang, 2024)
Natural flooding phenomena can be a disaster, which can cause life difficulties, loss of life, and property for affected humans. In 2022, a few points of the Kampwolker River that once spilled into the settlements could endanger the population. The objective of this study is to find out the mitigation of natural disasters at the site of the study, monitoring the hydrological conditions of the DAS. The results of the study show that 20 dangerous houses are located on the cliffs of the Kampwolker River, six electricity poles whose positions must be considered. Hydrological monitoring of rivers is carried out with effective rainfall 2 hours after rain. The river capacity is unable to accommodate the discharge in the middle section of 420.58 m3/sec and in the downstream section 447.91 m3/sec. Physical quality of the water is cloudy brownish, lots of sediment, odorless, the water quality class is in the heavy class. The material is found to be easily carried away by streams during heavy rain.